2023
DOI: 10.3390/ijms24098037
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Modulates the Response of Patient-Derived Metastatic Melanoma Cells to Anticancer Drugs

Abstract: Melanoma is considered a lethal and treatment-resistant skin cancer with a high risk of recurrence, making it is a major clinical challenge. Our earlier studies documented that 1,25(OH)2D3 and its low‑calcaemic analogues potentiate the effectiveness of dacarbazine and cediranib, a pan-VEGFR inhibitor. In the current study, a set of patient-derived melanoma cultures was established and characterised as a preclinical model of human melanoma. Thus, patient-derived cells were preconditioned with 1,25(OH)2D3 and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Relating to murine B16 melanoma, the reported differences in biological effects of vitamin D derivatives could be secondary to test conditions or simply use of different sublines of B16 melanoma [ 588 ]. A variety of vitamin D3 and D2 derivatives were tested including classical forms, chemically generated low calcemic forms, and CYP11A1-derived non-calcemic or low calcemic variants, all of them showing anti-melanoma activities on cultured melanoma cells [ 51 , 63 , 188 , 285 , 410 , 411 , 439 , 441 , 443 , 449 , 461 , 483 , 484 , 487 , 489 , 533 , 569 , 588 , 593 , 594 , 595 , 596 , 597 ]. In some melanomas, 1,25(OH) 2 D3 or its synthetic analogs showed proapoptotic effects, while in others there was a lack of such effect [ 188 , 598 ].…”
Section: Role Of Vitamin D In Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Relating to murine B16 melanoma, the reported differences in biological effects of vitamin D derivatives could be secondary to test conditions or simply use of different sublines of B16 melanoma [ 588 ]. A variety of vitamin D3 and D2 derivatives were tested including classical forms, chemically generated low calcemic forms, and CYP11A1-derived non-calcemic or low calcemic variants, all of them showing anti-melanoma activities on cultured melanoma cells [ 51 , 63 , 188 , 285 , 410 , 411 , 439 , 441 , 443 , 449 , 461 , 483 , 484 , 487 , 489 , 533 , 569 , 588 , 593 , 594 , 595 , 596 , 597 ]. In some melanomas, 1,25(OH) 2 D3 or its synthetic analogs showed proapoptotic effects, while in others there was a lack of such effect [ 188 , 598 ].…”
Section: Role Of Vitamin D In Melanomamentioning
confidence: 99%
“…Vitamin D derivatives not only have a direct anti-melanoma effect, but also can sensitize melanoma cells to different types of therapy [ 592 , 594 , 595 , 596 , 601 ]. For example, 1,25(OH) 2 D3 and 25(OH)D3 can sensitize melanoma towards proton beam therapy [ 601 ].…”
Section: Role Of Vitamin D In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown the direct effects of 1,25(OH) 2 D 3 on ion transport [31,32], including activity of mitochondrial membrane potassium channels [33]. Finally, pre-incubation with 1,25(OH) 2 D 3 significantly deepened the effect of anti-cancer drugs on the mitochondrial respiration of patient-derived melanoma cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have also explored whether 1,25(OH) 2 D 3 modulates the effectiveness of selected drugs, since we have shown that vitamin D and its analogue, calcipotriol, enhance the activity of a classical chemotherapeutic, dacarbazine, in human malignant A375 melanoma cell line [ 20 ]. Recently we also showed that 1,25(OH) 2 D 3 and other vitamin D derivatives significantly augment the efficacy of cediranib, an oral tyrosine kinase inhibitor of VEGFR1-3, PDGFR, and c-KIT, against A375 and SK-MEL-28 melanoma cell lines, out of four human cell lines that were tested, as well as against patient-derived melanoma cells [ 21 , 22 ]. What is more, there is a clear link between FGFRs signalling and vitamin D homeostasis, as loss of function in FGFRs leads to deregulation of Cyp27b1 and Cyp24a1 and the induction of hypervitaminosis D in a mouse model [ 23 ].…”
Section: Introductionmentioning
confidence: 99%